ANALISIS PENGARUH KUALITAS PRODUK, SALURAN DISTRIBUSI, DAN CELEBRITY ENDOSER TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus pada Pengguna Masker Wajah Mustika Ratu di Kota Semarang) - Nurlitasanti, Feby; Yoestini, Yoestini (Faculty of Economics and Business Diponegoro University, 2020)
Business competition in cosmetics products is increasing rapidly in line with the growth of the cosmetics industry every year in Indonesia. One of the leading cosmetic brands is Mustika Ratu. As the brand has been established for more than 42 years, Mustika Ratu has the proficiency and good reputation in producing cosmetics. The research aims to examine the effect of product quality variables, distribution channels, celebrity endorsers on purchasing decisions. Consumers who have used Mustika Ratu’s face mask products in Semarang City were chosen as the population in this study. The sample for this research is 100 respondents that were selected with purposive sampling through a questionnaire. The obtained data will then be processed and analyzed with the SPSS program. The results of this research show that the variable of product quality, distribution channels, and celebrity endorser had a positive and significant effect on purchasing decisions.